2015
DOI: 10.5530/ijper.49.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Stress among Undergraduate Pharmacy Students in University of Malaya

Abstract: Health care students, particularly pharmacy students, are believed to experience a higher level of stress as compared to their age-matched peers. This cross-sectional study determined the sources and predictors of stress among 273 undergraduate pharmacy students at a Malaysian public university using the Derogatis Stress Profile instrument. The response rate was 100%. Pearson's correlation was used to examine the association between Grade Point Average (GPA) and stress levels. Paired and Independent t-tests as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
4
16
0
Order By: Relevance
“…Other studies, however, agree with the findings in this study. A study carried out among students of a medical school in Malaysia did not find any significant gender difference in anxiety and stress of the students (Sun & Zoriah, 2015). A similar study conducted in Nigeria also did not find any significant gender difference in the prevalence of depression, anxiety and stress (Coker, Coker, & Sanni, 2018).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Other studies, however, agree with the findings in this study. A study carried out among students of a medical school in Malaysia did not find any significant gender difference in anxiety and stress of the students (Sun & Zoriah, 2015). A similar study conducted in Nigeria also did not find any significant gender difference in the prevalence of depression, anxiety and stress (Coker, Coker, & Sanni, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…In another recent study, over one-fourth of pharmacy students had high levels of depression, anxiety and stress (Sabourin, Prater, & Mason, 2018). Perceived stress was also found to be high among pharmacy students (Sun & Zoriah, 2015). Some studies have even reported a higher risk of stress in students studying pharmacy compared to students in other healthcare professions (Henning, Ey, & Shaw, 1998).…”
Section: Introductionmentioning
confidence: 91%
“…In contrast to the reviewed studies, one scholarly work compared the level of stress amongst medical, dental as well as the pharmacy students. The study found that pharmacy students were more prone to stress, an aspect which drastically reduced their overall academic performances (Al-Dubai et al, 2011;Sun and Zoriah, 2015). Previous researches have also indicated that many of these students wake up very early to study, which translates into a reduced time of sleep at night.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between high stress levels, low mental health-related quality of life and academic performance among pharmacy students have been reported [14, 17]. Yet, there is a dearth of information on stress and quality of life outcomes among pharmacy students in Ghana.…”
Section: Introductionmentioning
confidence: 99%